Profile of Kawasaki Disease in Adolescents: Is It Different? - Najib Advani; Lucyana Alim Santoso; Sudigdo Sastroasmoro (Acta Medica Indonesiana, 2019)
Background: there is clearly growing population of young adults with potentially important coronary artery disease after Kawasaki disease (KD) during childhood, and cardiologist must be prepared to take care for them. As Kawasaki disease in adolescent and adult is rare and under-recognized, it is important to study data on patient presentations which may permit development of diagnostic criteria and treatment guidelines for this age group.This study aimed to compare the clinical profile of KD between adolescents (>10 years of age) and children ≤10 years. Methods: This is a cross sectional study. A total of 1150 KD cases (age 1-192 months) during the period of January 2003-December 2016 were analyzed. The clinical profile of subjects aged >10 years (adolescents) and  ≤10 years (children) at acute phase of KD were compared. Results: we found 17 cases of KD in adolescents among 1150 total cases (1.5%). Incomplete KD was more often seen in adolescents compared to children ≤ 10 years of age (59% vs. 29%). Some clinical features were more frequently seen in children than in adolescents, e.g. conjunctivitis (85% in ≤ 10 years of age vs. 65% in > 10 years), mucosal changes (94% vs. 77%), rash (86% vs. 59%), and hand/foot changes (68% vs. 41%). While other clinical features were more often seen in adolescents, e.g., cervical lymphadenopathy (82% vs. 39%) and coronary dilatation (47% vs. 29%). Laboratory results (hemoglobin, leukocytes, erythrocyte sedimentation rate and C-reactive protein) did not differ much between the two groups. Conclusion: Kawasaki disease in adolescents has some different clinical profile from that of younger age. Majority of adolescent patients have incomplete presentation. Some clinical features such as conjunctivitis, mucosal changes, rash, and hand/foot changes are more often seen in children ≤ 10 years compared to in adolescents, while cervical lymphadenopathy and coronary dilatation are more frequently seen in adolescents. The ratio of male to female is much higher in adolescents.